2018
DOI: 10.1111/ecin.12550
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economics of the Arab Spring

Abstract: There were large differences in the responses of Arab dictators to the Arab Spring protests. To understand these differences, I present a stylized model of how a dictator responds to mass protests for democratization in a polarized country with two ethnic or religious groups. In this model, the dictator's response crucially depends on oil revenues and his affiliation to either the majority or the minority group. I document that the model's predictions are consistent with the observed differences in the Arab di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The MENA region has recognized the importance of diversifying corporate boards in order to improve corporate outcomes (Jamali et al, 2007;Loukil & Yousfi, 2016;Salloum et al, 2017). In the Arab world, the 2010 Arab spring has particularly orchestrated a wave of economic, financial, governance, and social changes, even in highly conservative and religious countries (Acemoglu, Hassan, & Tahoun, 2017;Hodler, 2018;Merrill, 2017;Salloum et al, 2017). For example, Saudi Arabia, a highly conservative Islamic country, has in an unprecedented manner, recently extended a number of major economic, financial, governance, political and social rights, and freedoms to women, such as banking, driving, political (e.g., to stand and be elected as political office holders), executive (e.g., to be appointed as directors), and voting rights, among others (Kamrava, 2012;Merrill, 2017;Salloum et al, 2017).…”
Section: Board Diversity Cg Ep and The Mena Corporate Contextmentioning
confidence: 99%
“…The MENA region has recognized the importance of diversifying corporate boards in order to improve corporate outcomes (Jamali et al, 2007;Loukil & Yousfi, 2016;Salloum et al, 2017). In the Arab world, the 2010 Arab spring has particularly orchestrated a wave of economic, financial, governance, and social changes, even in highly conservative and religious countries (Acemoglu, Hassan, & Tahoun, 2017;Hodler, 2018;Merrill, 2017;Salloum et al, 2017). For example, Saudi Arabia, a highly conservative Islamic country, has in an unprecedented manner, recently extended a number of major economic, financial, governance, political and social rights, and freedoms to women, such as banking, driving, political (e.g., to stand and be elected as political office holders), executive (e.g., to be appointed as directors), and voting rights, among others (Kamrava, 2012;Merrill, 2017;Salloum et al, 2017).…”
Section: Board Diversity Cg Ep and The Mena Corporate Contextmentioning
confidence: 99%
“…Studies have shown that the Arab Spring considerably changed the political landscape in the MENA region, enabling Islamists to move to the forefront of Arab politics as power holders (e.g., Al-Anani, 2012;Chamkhi, 2014;and Netterstrøm, 2015). In the meantime, countries have settled into diverse forms of government where autocratic and democratic features are combined (Miller et al, 2012;Roy, 2012;Abushouk, 2016), whereas ethnic politics and religious divides affect Arab dictators' responses to the Arab Spring protests (Hodler, 2018).…”
Section: Introductionmentioning
confidence: 99%